Health Status of Visitors and Temporary Residents, United States - Emad A. Yanni; Nina Marano; William M. Stauffer; Elizabeth D. Barnett; Maria Cano; Martin S. Cetron (Emerging Infectious Diseases, 2009)
Human mobility has always been associated with the spread of infection, and mobility of nonimmigrant visitors and temporary residents to the United States is increasing, from ≈12 million in 1987 to ≈37 million in 2007. Lack of information about the health status of these populations upon arrival and their need for and use of medical services in the United States hinders development of public health policy, education, and provision of adequate clinical care. After these issues and needs are clarified, intervention programs should be developed to increase access and decrease the disparities of care experienced by these populations.